Antifungal activity of Cymbopogon citratus against Colletotrichum gloesporioides - Pérez Cordero, Alexander Francisco; Chamorro Anaya, Leonardo Miguel; Vitola Romero, Deimer Calixto; Hernández Gómez, Jesús María (Agronomía Mesoamericana, 2017)
The objective of this research was to evaluate in vitro the inhibitory activity of essential oils from fresh leaves of Cymbopogon citratus (lemongrass) against Colletotrichum gloeosporioides in yam. The research was conducted in the department of Sucre, Colombia. The essential oils of C. citratus were collected in the municipalities of Sincelejo, La Union and Sampues, in September and October 2015. The essential oil was extract from fresh leaves using the microwave-assisted hydrodistillation. Concentrations of 5000, 8000 and 10 000 ppm of each essential oil were prepared. An absolute control, a positive control (benomyl 1 g/l) and a negative control was used. An inhibitory activity was obtained by using the direct seeding on surface of the potato-dextrose-agar method and it was expressed as percentage of inhibition rate. The chemical characterization of essential oils was performed by gas chromatography coupled to mass spectrometry. The highest percentages of antifungal index were observed in the lemongrass from Sincelejo at concentrations of 5000, 8000 and 10 000 ppm, after in La Union at 8000 and 10 000 ppm, and finally at Sampues at 10 000 ppm, with a value of 97.77%; the effect was similar to the positive control with benomyl 1 g/l. Citral was the main constituent of the essential oils extracted. The essential oils obtained from the three municipalities showed antifungal activity against C. gloeosporioides.